Analysis of Wear Properties of Hardox Steels in Different Soil Conditions - Ligier, Krzysztof; Zemlik, Martyna; Lemecha, Magdalena; Konat, Łukasz; Napiórkowski, Jerzy (Materials, 2022)
This paper presents the results of wear tests of three types of commercial abrasion-resistant steels. The samples, cut from commercially available sheets of metal, were subjected to wear tests to a total friction path of 20,000 m. The tests were provided using the “rotating bowl” method in three types of natural soil masses. The soil moisture and test parameters were kept constant. The tests were carried out in six replications for each material. The testing results indicate that hardness does not determine the resistance to abrasive wear, which is supported by the weight loss results for particular materials. Hardox 600 steel, which is not characterized by the highest hardness, exhibited the lowest weight loss value compared to the other materials in all test soils. For the light soil, the weight loss for Hardox 600 was approx. 1.3 times lower than for Hardox 500 steel and approx. 1.6 times higher than for Hardox Extreme steel. With regards to the medium and heavy soil, the weight losses for Hardox 600 in relation to Hardox 500 steel were approx. 1.7 and 1.6 times lower, respectively, while in relation to Hardox Extreme steel the weight losses were 1.5 and 1.7 times higher, respectively.